A longitudinal study of environmental tobacco smoke exposure in children: Parental self reports versus age dependent biomarkers - Sunyer Jordi; Zuccaro Piergiorgio; Pacifici Roberta; Monleon Toni; Garcia-Algar Oscar; Puig Carme; Figueroa Cecilia; Pichini Simona; Vall Oriol (BMC, 2008)
Abstract Background Awareness of the negative effects of smoking on children's health prompted a decrease in the self-reporting of parental tobacco use in periodic surveys from most industrialized countries. Our aim is to assess changes between ETS exposure at the end of pregnancy and at 4 years of age determined by the parents' self-report and measurement of cotinine in age related biological matrices. Methods The prospective birth cohort included 487 infants from Barcelona city (Spain). Mothers were asked about maternal and household smoking habit. Cord serum and children's urinary cotinine were analyzed in duplicate using a double antibody radioimmunoassay. Results At 4 years of age, the median urinary cotinine level in children increased 1.4 or 3.5 times when father or mother smoked, respectively. Cotinine levels in children's urine statistically differentiated children from smoking mothers (Geometric Mean (GM) 19.7 ng/ml; 95% CI 16.83-23.01) and exposed homes (GM 7.1 ng/ml; 95% CI 5.61-8.99) compared with non-exposed homes (GM 4.5 ng/ml; 95% CI 3.71-5.48). Maternal self-reported ETS exposure in homes declined in the four year span between the two time periods from 42.2% to 31.0% (p < 0.01). Nevertheless, most of the children considered non-exposed by their mothers had detectable levels of cotinine above 1 ng/mL in their urine. Conclusion We concluded that cotinine levels determined in cord blood and urine, respectively, were useful for categorizing the children exposed to smoking and showed that a certain increase in ETS exposure during the 4-year follow-up period occurred.